(untitled) (Heritage, 2022)
The paper discusses the issue of children’s rights from the perspective of presenting this topic to school students. It examines the opinions of college students – future teachers, on their level of preparedness for this role. States Parties to the Convention on the Rights of the Child, including Serbia, are tasked with establishing legislation and providing the conditions for its implementation, as well as with introducing the rights of the child in their educational policies. Serbian school curricula include the topics related to children’s rights (at all educational levels), with the intention of teaching school students about their rights and creating school situations in which they will be able to participate, thus developing civic skills. The responsibility for this task lies with the teachers. The paper reports on the self-assessments of college students – future teachers, regarding their knowledge of the Convention on the Rights of the Child and their preparedness, acquired during their academic studies, to present the content of the Convention to school students. The qualitative methodology of focus group discussions was chosen for achieving this objective, with the opinions of a total of 38 second-, third- and fourth-year students of the Faculty of Education in Sombor, divided into three focus groups, examined. The results suggest that future teachers assess the content on children’s rights and participation as highly significant and that they view the role of teachers in the promotion of these values as comparably important. They also believe that school students should learn about rights, but also participate in daily activities. College students pointed out that, during their academic studies, they have attended courses at which they were taught about children’s rights but that opportunities to implement such content in practice were lacking. Also, during their practical training in schools, they have not attended any classes or school situations in which children’s rights and participation were delineated. The conclusion is that to teach school students about children’s rights and participation more effectively, it is necessary to empower future teachers. A greater number of practical lessons, as well as the innovation of study programs focusing on the corpus of children’s rights, are seen as viable solutions.